(3EOGQI GdJaGhV (B/s - (3GdYdGb, HTjQs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3eaghe GdJaGhV , JYQjag h NUGFUg , GdGgejI h GdedGeM h GdeSJhjGJ h GdGfhGY GdNGUI HGdJaGhV , YfGUQ GdJaGhV h BdjGJg hhSGFd GdJMce Hg ,BdjGJ GdJaGhV h egGQGJg (B.s
(3eQGLY U(B.222s
Keywords: (3GdJaGhVs; (3GdJaGhV `` EOGQIs; (3GdeaGhVGJs